Perceptions on environmental education at the Higher Education Institute (Research, Society and Development, 2019)
The article, presented here, the result of a research, was to identify and describe the actions and ways of seeing environmental education (EA) in undergraduate courses of the Higher Institute of Education (ISE), an instance linked to the University Anápolis (UniEvangélica). Because it was a case study, the questionnaire was used as an instrument to collect data with teachers and students of undergraduate courses in chemistry, mathematics, biology, letters, history and pedagogy of the institution. The result was descriptive and exploratory, in which the qualitative discussion was discussed under the light of the environmental and environmental literature. As a result of the study, in the view of the subjects involved, the ISE has acquired a greater perception of environmental issues, through activities and research that focus on environmental issues and environmental education.